Matching high-risk recipients with marginal donor organs is a clinically effective strategy - Russo, Mark J. (2009)
BACKGROUND: The purpose of this study is to determine the clinical outcomes associated with Alternate Listing Transplantation (ALT) strategies. METHODS: UNOS provided de-identified patient-level data. Primary analysis focused on patients undergoing heart transplantation between January 1, 1999 to December 31, 2005 (n=13,024). HR criteria included age [gt] 65yo, retransplantation, HepC+, HIV+, CrCI [It] 30 ml/min, DM with PVD, DM with Crcl [It] 40 ml/min. MD criteria included age [gt] 55yo, DM, HIV+, HepC+, EF [It] 45%, and dononrecipient weight [It] 0.7. RESULTS: Survival in the standard transplant group was better than all other groups (p<0.001). With a median survival of 5.2 years, long-term survival was worst in the alternate listing transplant group (p<0.001). The standard transplant group also had the best transplant hospitalization outcomes, having the lowest incidence of in-hospital infection and dialysis (p<0.001). Alternate listing transplantations had the highest incidence of in-hospital infection (p≤0.001). As expected, LOS for the transplant hospitalization was also shortest for standard list transplants, (p<0.001). CONCLUSIONS: Pairing high-risk recipients with marginal donors is associated with greater morbidity and resource utilization compared with standard recipients and donors. Nevertheless, this strategy offers 5 years or more of additional survival to patients who otherwise would be expected to live 1 year or less. Therefore, ALT strategies appear to be a reasonable approach to extending the benefits of transplantation in the heart failure population. However, further studies examining the costs and quality of life related to this approach are needed.